Identifying the frequency and connectivity dynamics of the US economy - Mathias Schneid Tessmann; Marcelo de Oliveira Passos; Omar Barroso Khodr; Alexandre Vasconcelos Lima; Pedro Henrique Pontes Fontana (Economies, 2024)
This paper seeks to investigate the connectivity of the US economy through the dynamics of the transmission of volatility in sectoral indices. For this, we use daily asset data and two methodologies. The first creates a spillover index that measures market connectivity and the second partitions this index into different frequency bands that denote periods. We found results that show significant transmissions of volatility among the 64 analyzed assets. Notably, the DJIA, Wilshire 5000, and S&P 500 showed significant volatility and were the main drivers of volatility for the other sectors and indices. Results also indicated that sectors that transferred volatility were influenced by three key factors: periods of economic uncertainty, socioeconomic circumstances resulting from post-crisis events, and the impact of economic and financial news on market sentiment. Additionally, we found that global returns and price changes in market indices sent considerable volatility into commodity assets. Our results are potentially useful for investors, portfolio managers, financial economists, financial advisors, financial market regulators, and policymakers.
Keywords: E30; E44; G01; G10; 330; frequency decomposition; post-crisis volatility; spillover index; volatility transmission